Comparison of subclinical coronary atherosclerosis and risk factors in unselected populations in Germany and US-America - Schmermund, Axel; Lehmann, Nils; Bielak, Lawrence F.; Yu, PanFong; Sheedy, Patrick F.; Cassidy-Bushrow, Andrea E.; Turner, Stephen T.; Moebus, Susanne; Möhlenkamp, Stefan; Stang, Andreas; Mann, Klaus; Jöckel, Karl-Heinz; et al. (Atherosclerosis, 2007)
On the basis of the Framingham risk algorithm, overestimation of clinical events has been reported in some European populations. Electron-beam computed tomography-derived quantification of coronary artery calcification (CAC) allows for non-invasive assessment of coronary atherosclerosis in the general population and may thus add important in vivo information on the path from risk factor exposure to formation of clinical events. The current study was undertaken to compare the relationship between risk factors and subclinical coronary atherosclerosis between non-Hispanic white cohorts in Germany and US-America, the hypothesis being that subclinical coronary atherosclerosis might be less prevalent in Europe at the same level of classical risk factor exposure. The Heinz Nixdorf Recall (HNR) study, conducted in the German Ruhr area and the Epidemiology of Coronary Calcification (ECAC) study, conducted in Olmsted County, Minnesota, both recruited large unselected cohorts, men and women aged 45–74 years, from the general population. All subjects with no history of coronary artery disease (CAD) or stroke were included ( n = 3120 in HNR, n = 703 in ECAC). Coronary risk factors were assessed by personal and computer-assisted interviews and direct laboratory measurements. Cardiovascular medication use (antihypertensive, lipid-lowering, and anti-diabetic) was noted. CAC scores were determined using the Agatston method in an identical fashion in both studies. Adverse levels of risk factors were more prevalent, and the Framingham risk score was higher (10.6 ± 7.6 versus 9.3 ± 7.1, p < 0.001) in HNR than ECAC, respectively. There was no difference in body mass index (BMI). CAC scores were greater in HNR than in ECAC (mean values, 155.7 ± 423.0 versus 107.2 ± 280.0; median values, 11.9 versus 2.4; p < 0.001, respectively). When subjects were matched on CAD risk factors, presence and quantity of CAC were similar in the 2 cohorts. Risk factors significantly associated with CAC score in both studies included: age, male sex, current and former smoking, systolic blood pressure, and non-HDL-cholesterol. Inferences were similar after excluding subjects using lipid- or blood pressure-lowering medications. Using the same risk factor variables for modelling, the predicted CAC scores were comparable in both cohorts. In the higher-risk German cohort, presence and quantity of CAC were greater than in the lower-risk US-American cohort. Risk factor associations with CAC were very similar in both unselected populations. We could not demonstrate a relative increase in subclinical coronary atherosclerosis in the US-American cohort. It appears possible to compare CAC as a measure of subclinical coronary artery disease in different populations on different continents, and accordingly, scanning guidelines might be translated across these populations.